The Conservation of Biodiverse and Threatened Dry Rainforest Plant Communities Is Vital in a Changing Climate - Marion Howard; Hilary Pearl; Bill McDonald; Yoko Shimizu; Sanjeev Kumar Srivastava; Alison Shapcott (Conservation)
Dry rainforest communities are globally threatened by anthropogenic pressures and climatic change but are less well researched and more poorly conserved than mesic rainforests. In response to the increasing loss of biodiversity, the Australian Government joined other international signatory parties to adopt the Kunming-Montreal Global Biodiversity Framework (GBF). The GBF emphasises the maintenance of connectivity and genetic diversity of whole ecosystems via landscape-scale conservation initiatives. Rainforest plant diversity, distinctiveness, and the current level of conservation of seasonal rainforest regional ecosystems of the Central Queensland Coast region in Australia were evaluated. Our three-marker DNA barcode dated phylogeny of rainforest plant taxa together with community species lists were used to calculate phylogenetic diversity (PD) estimates and species composition. Levels of rainforest ecosystem protection were assessed using Queensland government data. This study found selection pressures for moisture and geology significantly influence rainforest distribution and species diversity and evidence of a high degree of variability in terms of conservation. While some phylogenetically distinctive rainforest community types were well conserved, restricted or endangered communities were very poorly protected. Additionally, we found smaller dry rainforests in the Central Queensland Coast represent regional plant migration but are inadequately protected, highlighting the need for a revision of conservation objectives within the region.